Impact of silica deposition on the performance of gas-fired domestic appliances caused by the combustion of siloxanes in the fuel. (March 2019) - Gersen, Sander; Visser, Pieter; van Essen, Martijn; Brown, Martin; Lewis, Andy; Levinsky, Howard
Abstract: The effects of silica deposition resulting from the combustion of siloxane-containing biomethane on the performance of seven domestic appliances have been studied. The results show that silica deposition increases the flow resistance across the heat exchangers, which consequently reduces the air intake from the surroundings. For the flow-through hot water heater studied, the reduction in air intake in the appliance results in a substantial increase in the CO emission with time, ultimately resulting in a safety risk for the end user. For the fully premixed boilers examined, the increased flow resistance reduces the thermal input, and thus the thermal output, of the appliance. The extent of the reduction in thermal input is seen to depend strongly upon the concentration silicon in the fuel, and the configuration and material of the heat exchanger. For the boilers studied, the ion current measured by the flame safety device decreases with time because silica deposits on the probe used to measure the current in the flame; this ultimately results in boiler failure. Based on the results, extrapolation methods are proposed that can be used to assess the impact of low silicon concentrations in biomethane on appliance performance and safety with time. Highlights: Impact of combustion of siloxanes in biomethane on performance of domestic appliances. Silica deposition in heat exchangers reduces the air intake from the surroundings. Increased in CO emissions observed in flow-through hot water heater with time. Reduced thermal input and output observed in high-efficiency boilers. Silica deposition on ionization safety probe with time results in appliance failure.